AB0125 Anti-dengue igg antibody positivity and risk of developing rheumatoid arthritis: evidence from the malaysian epidemiological investigation of rheumatoid arthritis (MYEIRA) case-control study. (12th June 2018) - Tan, L.K.; Ahmad Fauzi, N.A.; Sulaiman, W.; Ali, O.; Lau, I.S.; Hussein, H.; Sharil, N.S.; Gun, S.C.; Mageswaren, E.; Mohd-Said, M.-S.; Mohd-Mokhtar, A.; Rosman, A.; et al.
Abstract : Background: Arthralgia is one of the common symptoms seen in RA and in mosquito-borne viral diseases (dengue and chikungunya infections). Studies have reported that both dengue and chikungunya infections are associated with long-term persistent rheumatic symptoms including joints, muscle and bone pain. Objectives: We investigated the association between anti-dengue IgG antibody positivity and risk of developing anti-citrullinated peptide antibody (ACPA)-positive and ACPA-negative RA in the multi-ethnic Malaysian population. Methods: A total of 1147 early RA cases (515 Malay, 254 Chinese and 378 Indians) and 1519 age, sex and residential area matched population-based controls (1, 023 Malay, 208 Chinese, and 288 Indians) were included in this study. Anti-dengue IgG antibody was determined by ELISA method. The presence of anti-dengue IgG antibody and risk of developing ACPA-positive/ACPA-negative RA were estimated by calculating the odds ratio (OR) with 95% confidence interval (95% CI). Results: Our data demonstrated that 79.1% (n=1, 003) and 77.1% (n=1, 255) RA and control subjects were positive for anti-dengue IgG antibody, respectively. Data analysis revealed that the Chinese RA patients has highest frequency of anti-dengue IgG antibody (86.6%) followed by the Indian (80.4%) and Malay (74.4%) RA patients while 83.7%, 87.5% and 73% Chinese, Indian and Malay healthy controls were positive for this antibody, respectively. The anti-dengue IgG antibody positivity was significantly associated with decreased risk of RA in the Indian population (OR 0.59, 95% CI: 0.38–0.91, p=0.02) and particularly for the ACPA-positive subset of RA (OR 0.60, 95% CI 0.37–0.96, p=0.03). Interestingly, we observed a non-significant increased risk for ACPA-positive RA in the Chinese (OR 1.49, 95% CI 0.81–2.72) and Malay populations (OR 1.06, 95% CI: 0.79–1.41) with anti-dengue IgG antibody. No association was observed between ACPA-negative RA and the antibody positivity. Conclusions: Our study describes the association between anti-dengue IgG antibody occurrence and ACPA-positive RA, but not ACPA-negative RA in an ethnicity-dependent manner. Future research is needed to explore the biological mechanisms behind these findings. References: [1] Mohd Zim MA, et al. Chikungunya infection in Malaysia: Comparison with dengue infection in adults and predictors of persistent arthralgia. Journal of Clinical Virology2013;56(2013):141–145. [2] Gissel Garcı et al. Long-term persistence of clinical symptoms in dengue-infected persons and its association with immunological disorders. International Journal of Infectious Diseases2011;15(2011):e38–e43. Disclosure of Interest: None declared